SPATIAL SEGREGATION AND SOCIOECONOMIC DISPARITIES IN URBAN LAND USE PATTERNS - Lestari, Intan; Hasibuan, Hayati Sari; Ardiwijaya, Vevin Syoviawati (UI Scholars Hub, 2024)
Jakarta, a city that has continued to develop, is marked by the growth of population in Jakarta. This growth has been accompanied by an increasing demand for land, resulting in spatial segregation. Some areas have large expanses of land, while others are densely populated and cramped. The purpose of this study is to analyze spatial segregation in the Penjaringan and Pluit Subdistricts of North Jakarta. The research employs a qualitative descriptive analysis method, spatial analysis using Moran's and Getis-Ord Gi*, and a literature review enriched with interviews. The research findings indicate clear spatial segregation between Pluit and Penjaringan, divided into positive and negative hotspot clusters representing larger vs. very narrow land parcels. It is also shown by the clustering pattern with the 0.03 Moran index value. The contrast in segregation depicts demographic and socioeconomic characteristics between the two areas. This pattern is also similar to the land value zones, where Penjaringan has lower land values than Pluit. These findings underscore the pressing need for inclusive urban planning strategies to address spatial disparities. Policies that promote shared public spaces, equitable infrastructure distribution, and mixed-use development could help bridge the socioeconomic divide. By integrating spatial equity into planning practices, urban development can foster greater social cohesion and ensure that the benefits of growth are more evenly distributed across all areas. This approach is vital for creating sustainable and inclusive urban environments.